PAX2 is dispensable for in vitro nephron formation from human induced pluripotent stem cells - Yusuke Kaku (Nature Portfolio, 2017)
Abstract The kidney is formed by reciprocal interactions between the nephron progenitor and the ureteric bud, the former of which gives rise to the epithelia of nephrons consisting of glomeruli and renal tubules. The transcription factor PAX2 is essential for this mesenchymal-to-epithelial transition of nephron progenitors, as well as ureteric bud lineage development, in mice. PAX2 mutations in humans cause renal coloboma syndrome. We previously reported the induction of nephron progenitors and three-dimensional nephron structures from human induced pluripotent stem (iPS) cells. Here we generate iPS cells lacking PAX2, and address the role of PAX2 in our in vitro induction protocol. While PAX2-null human nephron progenitors were properly formed, they unexpectedly became epithelialised to form glomeruli and renal tubules. However, the mutant glomerular parietal epithelial cells failed to transit to the squamous morphology, retaining the shape and markers of columnar epithelia. Therefore, PAX2 is dispensable for mesenchymal-to-epithelial transition of nephron progenitors, but is required for morphological development of glomerular parietal epithelial cells, during nephron formation from human iPS cells in vitro.